Enhancing recombinant T1 lipase production in Pichia guilliermondii - Ladidi, Abu Mary (2017)
Lipases are hydrolytic enzymes, ranked as third most relevant industrial enzymes with 5 % share in global enzyme market. Thermostable T1 lipase from Geobacillus zalihae was previously expressed under the regulatory control of alcohol oxidase promoter 1 (AOXp 1) in the methylotrophic yeast Pichia guilliermondii, isolated from spoiled orange. Methanol was found to be a vital compound to induce the promoter activity in Pichia pastoris. In this study P. guilliermondii has shown the potential to express the recombinant lipase without methanol under the regulation of AOXp 1. This study sought to optimise medium conditions of thermostable lipase with and without methanol as inducer. The expression of T1 lipase without methanol was expected to reduce cost and toxicity effect of methanol. Buffered and non-buffered media compositions were studied for T1 lipase production, the media were first, supplemented with methanol then without methanol. Buffer complex methanol medium was observed to be optimum for T1 lipase production with a 3-fold increase over non-buffered methanol medium. One-factor-at-a-time, conventional method of optimisation was used to identify significant data range for medium parameters. Using the observed data range, eight parameters which includes temperature, pH, inoculum size, biomass concentration, incubation time, shaking speed, culture volume and methanol concentration, were screened for lipase production in methanol medium using Plackett-Burman Design. Temperature, inoculum size, culture volume and incubation time, were observed to exert significant effect on lipase production. These parameters were optimised using Box-Behnken Design of Response Surface Methodology. Optimum levels of these parameters were predicted at temperature 34 oC, culture volume 190 mL, inoculum size 4 v/v and incubation time 24 h with an experimented lipase activity of 9.26 U/mL. Over 2-fold increase before optimization in methanol medium was observed and 6-fold increase over previous research work. On the other hand, six parameters which include temperature, pH, inoculum size, incubation time, shaking speed and culture volume were screened for T1 lipase production in medium without methanol. Three parameters were observed to have significant effect on lipase production, then, these parameters were further optimised using Box-Behnken Design and their optimum levels were achieved at pH of 6, inoculum size 2 v/v and incubation time of 24 h as was predicted and the experimented lipase activity of 2.012 U/mL was observed. This result gave 4-fold increase over lipase production before optimisation in medium without methanol. Recombinant T1 lipase production was further scaled up to 3 L in the bioreactor for 128 h in methanol medium and lipase activity observed was 12 U/mL at 120 h incubation time. Meanwhile, scale up in medium without methanol yielded a lipase activity of 3.5 U/mL at 118 h incubation time. The result has proven that, the time taken for optimum lipase production without methanol was faster from the production with methanol in the bioreactor. In conclusion, temperature, pH, inoculum size, incubation time and culture volume for recombinant T1 lipase production were optimised in shake-flask and applied to the bioreactor level. Lipase was also produced in medium without methanol both at the shake flask level and the bioreactor. Thus, medium parameters optimisation has proven to be very useful in enhancing thermostable lipase production in recombinant P. guilliermondii. Although T1 lipase has been expressed in medium without methanol but it is lower compared to medium with methanol.